TOOLPATH GENERATOR FOR MULTI MATERIAL FREEFORM FABRICATION (MMFF) PROCESS - Prahasto, Toni; Widyanto, Susilo Adi (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2007)
Fabrication of Rapid Prototyping (RP) of a mechanical part using multi-material powder-deposition is carried out to improve the functional aspect as well as the life time. This RP allows the multi-material fabrication by modifying the material delivery subsystem.This paper reports the fabrication of multi-material free-form parts, hereafter will be abbreviated as MMFF. This paper also presents a method of tool-path generation. The shape and the size of the part are the input of the RP-process; typically, this input is either a 3D-model from a CAD system or a set of coordinates from a CMM. In this report, the input is obtained from a CAD system. The model is sliced at a pre-determined thickness interval, and the results are a set of 2D sections. A section contains a single outer loop and may have inner loops. A tool path is generated for each section, and the path will later be traversed by a deposition nozzle. Scanning gaps between two parallel path is determined based on the geometry of the loops of the section. Tool path generator also facilitates the inputting setting data to appropriate the dimension machine capacity.